Analisis Bauran Pemasaran Jasa Dengan Keputusan Pembelian Layanan - Siti Alfani; Bagoes Widjanarko; Ayun Sriatmi (Jurnal Keperawatan Silampari, 2023)
This research aims to analyze the relationship between the 7P service marketing mix and service purchasing decisions at Sultan Fatah Regional Hospital, Demak. This research was conducted using a quantitative method with a Cross-Sectional Study approach. The statistical results show that the 7P marketing mix for each product element (p=0.008), price (p=0.000), place (p=0.011), promotion (p=0.028), people (p=0.017), process (p =0.021), physical evidence (p=0.007). In conclusion, the service marketing mix significantly positively impacts service purchasing decisions at Sultan Fatah Regional Hospital, Demak. Keywords: Services Marketing Mix, 7P Marketing Mix, Purchasing Decisions